Failure and Risk Analysis based on Maintenance Reports of Machines Components in Manufacturing Industry - Thamm, Aleksandra; Herz, Matthias; Wiedemann, Markus; Thamm, Florian; Maier, Andreas (XIII. International Conference on the Theory of Machines and Mechanisms - TMM2020, 2021)
Manufacturing engineering is concerned with the application of engineering practices in manufacturing processes and production methods. Continuous optimization of processes, tools as well as machinery and equipment is the key to producing quality products with optimal capital investment. Hereby, maintenance plays a crucial role and allows manufacturers to optimize their processes. To enable improvements in this field it is required to analyze and evaluate the necessities for actions on component level. In this work we want to present a detailed retrospective analysis of more than 4.000 maintenance reports and analyze causes for assembly failures depending on the associated components. Furthermore, we extend the analysis and investigate the failure dependency with respect to the days elapsed from the date of maintenance request to resolving the issue. It turned out, not all cases with high failure rates are associated with subsequent higher risks considering the respective urgency related to each failure case. Furthermore, we discovered especially hydraulic and pneumatic components have a significant high to critical risk, as the labour safety and other components are threatened by their failure. Moreover we determined, that only 10% of all actions were planned maintenance and thus we propose based on the results of the risks analysis, how planned and preventive maintenance should be extended to reduce costs in this regard.<br
Keywords: Manufacturing; Failure Analysis; Risk Analysis; Spare Parts; Maintenance; Preventive Maintenance